Cosmetic Packaging Design: A Case Study on Gender Distinction - Siripuk Ritnamkam; Nopadon Sahachaisaeree (My University, 2012)
This research aims to investigate a distinctive perceptual response between young males and females on graphical and packaging appearance leading to their buying decision. The research endeavors to reveal distinctive graphical and formal design factors determining packaging preferences in accordance with the level of cognitive and affective sensory between genders. The research found that shape, colour, element and principle correspond to young purchasers' gender difference. Research tools comprise distinctive visual stimulus set embedded with the contradictory factors, and questionnaires set to draw perceptual reactions. Sampled respondents are drawn from 19-23 graduate and undergraduate students from Department of Industrial Design and Education.
Keywords: Stimulus (psychology); Consumer Packaging Perceptions and Trends